The performance improvement of an automatic tire air filed and air pressure display system-an analysis of sustainability development - Gopal R.; Sharma A.; Gupta S.K.; de Liz E.M.; Teston S.F.; Kumar R. (My University, 2025)
The current research study provides the protection and solution to a car owner when the engine startup this system automatically and checks whether the tires are puncher or not; if the tire has puncher it will maintain a constant pressure in-order to facilitate the driver and allows him reach to the destination without repairing the tire. It possesses a button that facilitates driver to send a notification to the nearest service centre constituting the complete details and current condition of the tire that it has to be repaired or needs entire change. When the driver starts driving, it measures the pressure in all 2-Tires (For 2-W), 4-tires (For four-W), 6-tires (For six-W); moreover, distributes the air, according to its speed for maximum grip. A vehicle is moving with many high-speed drivers cannot handle the car at this speed effectively which causes accidents; therefore, the experienced drivers fill their tires with air-pressure not to its full potential so that the tire remains a little inflated with more grip to the road. It results in the better handling which will pump air to the tires according to car speed in real-time. If the tire gets puncher on the way, it will glow an indicator about the condition of the tire and helps to hold the tires pressure till we reach to our destination. It also consists of help button which alerts nearest service station about the condition of the tire, if it has to be repaired or completely changed; or the driver wants to adjust the pressure of the tire manually by using the display on the car dashboard. This system uses nitrogen gas which maintains the temperature of the tire, and as it is lightweight, it increases mileage. © 2020 SERSC.